Uji Aktivitas Antioksidan, Kandungan Fenolik Total, dan Kandungan Flavonoid Total Buah Merah - NI MADE DWI SANDHIUTAMI; A.A WIWIEK INDRAYANI (JURNAL ILMU KEFARMASIAN INDONESIA, 2012)
Antioxidants are compounds which have ability to inhibit free radical reactions in the human body. Objectives of this research are to evaluate the antioxidant activities of extract and fractions from Pandanus canoideus Lam. fruits, to determine total phenolic and total flavonoid contents, and to correlate the total phenolic and total flavonoid contents of those fractions with their antioxidant activities. The Pandanus conoideus Lam. fruits or locally known as “buah merah” were extracted by methanol, then evaporated and dissolved in aquadest. This solution is subsequently partitioned using chloroform and ethyl acetate to obtain chloroform, ethyl acetate, and water fractions. The antioxidant activities were determined by radical scavenging assay using DPPH (2,2-diphenyl-1-picrylhydrazyl) radical. The total phenolic and total flavonoid contents were determined by mean of spectrophotometry. The results showed that fractions of water, ethyl acetate, and chloroform revealed antioxidant activities with IC50 values of 399.06, 10.41, 1416.68 µg/mL respectively, whereas the methanolic extract of Pandanus conoideus Lam. fruits before partition has IC50 of 186.31 µg/mL. The antioxidant activities of these extract and fractions are lower than that of vitamin E (IC50 8.27 µg/ml). A linier positive relationship existed between the total phenolic contents of these extract and fractions with their antioxidant activities as shown by equation of y = 13.085x + 754.91; r2 = 0,3641, while the correlation between the total flavonoid contents and their antioxidant activities revealed a linier regression of y = -282.9x + 868.05; r2 = 0.4484.